Tax Planning, Profitability And Liquidity On Company Value With Corporate Transparency As A Moderation Variable - Heni Suryanti (Yayasan Riset dan Pengembangan Intelektual, 2023)
This research aims to analyze and explore the influence of Tax Planning, Profitability and Liquidity on Company Value with Company Transparency as a moderating variable in Mining Companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The data source in this research uses secondary data, namely the Mining Company's annual financial report for the 2016-2020 period. The research population was 53 Mining Companies for the 2016-2020 period. This research uses a purposive sampling method and there are 21 company samples processed using Eviews 12. The results of the research show that Tax Planning has a significant negative effect on Company Value, Profitability has a significant positive effect on Company Value, while Liquidity has no effect on Company Value. Company Transparency can moderate the influence of Tax Planning on Company Value and Profitability on Company Value but cannot moderate the influence of Liquidity on Company Value.